Оцінювання стратегії підприємства методом теорії ігор - Коваль, З. О.; Koval, Z. O. (Видавництво Львівської політехніки, 2021)
Запропоновано методику вибору і оцінювання стратегій підприємств за допомогою застосування теорії ігор, що дасть змогу врахувати стратегії конкурентів (інших учасників конфліктної ситуації) або стан “природи”, що уособлює середовище функціонування підприємств. Розглянуто переваги і недоліки застосування методів теорії ігор у сфері оцінювання стратегій підприємств, здійснено класифікацію та порівняння видів цих методів з метою з’ясування особливостей використання їх у визначених ситуаціях, досліджено особливості застосування критеріїв вибору стратегій у цій сфері.

The choice of strategy ensures the formation of a certain option that provides a detailed analysis of situations that may arise in the future. As in the game, where each of the participants plans their actions, predicting the actions of other players and the general conditions of situations that may arise as a result of these actions. You should pay attention to the probability of committing players and the probability of a certain situation. It is clear that this is a prediction of a situation that has not yet occurred, but occurred in accordance with the probability of the strategy in the implementation of the actions of each of the participants associated with the risk. The application of the principles, methods and tools of game theory will make it possible to form a complete plan of action in all situations that are expected to occur. The developed action plan of the participants (players, subjects) in accordance with the whole set of situations and possible developments in them, forms a strategy. Game theory is based on the application by each participant of a single strategy, which is a certain algorithm of actions, not a list of them. Such an algorithm, due to its branches, should reflect the possibility of occurrence and development of events and situations. The article proposes methods of selecting and evaluating enterprise strategies through the application of game theory, which will take into account the strategies of competitors (other participants in the conflict situation) or the state of “nature”, which embodies the environment of enterprises. The article considers the advantages and disadvantages of using game theory methods to evaluate enterprise strategies, classifies and compares the types of these methods to clarify the peculiarities of their application in certain situations, the peculiarities of the application of strategy selection criteria in this scope.
Evaluation of the enterprise strategy by the game theory method
Keywords: стратегія підприємства; ефективність стратегії; методи теорії ігор; алгоритм застосування теорії ігор для оцінювання ефективності стратегії підприємства; методика вибору стратегії підприємства; enterprise strategy; efficiency strategies; methods of game theory; algorithm of application of game theory for estimation of efficiency of enterprise strategy; methods of choice of enterprise strategy; 338.24; 658.152; 621